2010
DOI: 10.1103/physrevb.82.205436
|View full text |Cite
|
Sign up to set email alerts
|

Interface Landau levels in graphene monolayer-bilayer junctions

Abstract: Electronic structure of graphene monolayer-bilayer junction in a magnetic field is studied within an effective-mass approximation. The energy spectrum is characterized by interface Landau levels, i.e., the locally flat bands appearing near the boundary region, resulting in a series of characteristic peaks in the local density of states. Their energies are independent of boundary types such as zigzag or armchair. In the atomic scale, the local density of states shows a Kekulé pattern due to the valley mixing in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 63 publications
(83 reference statements)
1
34
0
Order By: Relevance
“…In experimentally produced bilayer graphene or graphene flake, it is often observed that the top-layer is interrupted suddenly while the bottom-layer still keeps going [6,7]. Based on promising electronic properties of hybrid bilayer/monolayer graphene experimentally synthesized by epitaxial growth, investigating thermal properties of these structures is important in thermal management of electronic devices as well as thermoelectric applications [8,9,6,10,11,12]. In such a hybrid layered nanostructure, the step-like configurations can be considered as an interface or intercept which imposes significant effects on electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In experimentally produced bilayer graphene or graphene flake, it is often observed that the top-layer is interrupted suddenly while the bottom-layer still keeps going [6,7]. Based on promising electronic properties of hybrid bilayer/monolayer graphene experimentally synthesized by epitaxial growth, investigating thermal properties of these structures is important in thermal management of electronic devices as well as thermoelectric applications [8,9,6,10,11,12]. In such a hybrid layered nanostructure, the step-like configurations can be considered as an interface or intercept which imposes significant effects on electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the limit ∆ → 0, this solution reduces to the one used in Ref. 32 in the description of interface states on the monolayer-bilayer graphene junction. The boundary conditions at the zigzag edge y = 0 of the half plane (which corresponds to η = −kl) are 24 Ψ s ξAi (−kl) = 0, i = 1, 2;…”
Section: A Dispersion Equations For Half Planementioning
confidence: 98%
“…The wave functions are distributed in the piecewise form near the interface between two regions, where the distorted bilayer and monolayer Landau wave functions are joined. [398] But for W t = 2W b /5 and d s = (W b − W t + b)/2 ( Fig. 39(b)), there are two monolayer-like QLLs, one bilayer-like QLLs, and two extra groups of intermediate Landau subbands, reflecting the geometric structure with two interfaces.…”
Section: A Magneto-electronic Propertiesmentioning
confidence: 99%